2016
DOI: 10.1103/physrevd.94.025040
|View full text |Cite
|
Sign up to set email alerts
|

Moving mirrors and the fluctuation-dissipation theorem

Abstract: We investigate the random motion of a mirror in (1 + 1)-dimensions that is immersed in a thermal bath of massless scalar particles which are interacting with the mirror through a boundary condition. Imposing the Dirichlet or the Neumann boundary conditions on the moving mirror, we evaluate the mean radiation reaction force on the mirror and the correlation function describing the fluctuations in the force about the mean value. From the correlation function thus obtained, we explicitly establish the fluctuation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…This is in contrast to the situation that was observed for a moving mirror in Minkowski spacetime when the velocity of the mirror is small; i.e. in the nonrelativistic limit [7,8]. However, this does not mimic gravity.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…This is in contrast to the situation that was observed for a moving mirror in Minkowski spacetime when the velocity of the mirror is small; i.e. in the nonrelativistic limit [7,8]. However, this does not mimic gravity.…”
contrasting
confidence: 70%
“…In the case of Brownian motion, it has been observed that the Fourier modes,K + (ω) andK − (ω), of these in the frequency domain are related by [7,18] …”
Section: Fluctuation-dissipationmentioning
confidence: 99%
“…With the progress of these investigations of particle production, some authors have taken further initiatives to address a spontaneous question in this context that, "how these produced particles behave, with respect to the particular observer who is detecting their existence?" [21][22][23]. The authors of [21], have investigated the random motion of a moving mirror, which is immersed in a thermal bath of massless scalar particles.…”
Section: Contentsmentioning
confidence: 99%
“…[21][22][23]. The authors of [21], have investigated the random motion of a moving mirror, which is immersed in a thermal bath of massless scalar particles. They have calculated the mean radiation reaction force on the mirror as exerted by the scalar particles and the correlation function of the fluctuations in the force about the mean value.…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation